RNA pol II Dynamics Modulate Co-transcriptional Chromatin Modification, CTD phosphorylation and transcriptional direction - Fong, Nova (Mol Cell, 2017)
Eukaryotic genes are marked by conserved post-translational modifications on the RNA pol II CTD and the chromatin template. How the 5′–3′ profiles of these marks are established is poorly understood. Using pol II mutants in human cells we found that slow transcription repositioned specific co-transcriptionally deposited chromatin modifications; H3K36me3 shifted within genes toward 5′ ends and H3K4me2 extended further upstream of start sites. Slow transcription also evoked a hyperphosphorylation of CTD Ser2 residues at 5′ ends of genes that is conserved in yeast. We propose a “dwell-time in the target zone” model to explain the effects of transcriptional dynamics on establishment of co-transcriptionally deposited protein modifications. Promoter-proximal Ser2 phosphorylation is associated with longer pol II dwell time at start sites and reduced transcriptional polarity due to strongly enhanced divergent antisense transcription at promoters. These results demonstrate that pol II dynamics help govern the decision between sense and divergent antisense transcription.